2001
DOI: 10.1021/la001124s
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Adsorption by Chitosan Impregnated with Microemulsion

Abstract: Removal of chromium(III) from aqueous solutions by chitosan impregnated with a microemulsion was investigated. The modified chitosan showed a remarkable increase in chromium sorption capacity as compared to an untreated sample. Dynamic column experiments were performed to study the influence of pH, concentration, and the presence of others metal ions (copper and nickel) in the chromium solutions. The adsorption process is pH-dependent, and the amount of Cr(III) retained increases with increasing heavy metal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
38
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 18 publications
5
38
0
2
Order By: Relevance
“…5,6 Chitosan is a hydrophilic, natural cationic polymer formed by the N-deacetylation of chitin, 7 which is present in fungi, insects, and crustaceans. Chitosan has been known for its metal adsorption properties since 1970s, 7,8 and it has been shown to effectively remove metals such as silver, 8 cadmium, 9 arsenic, 10 gold, 11,12 vanadium, 13 copper, [14][15][16] nickel, 14,17 chromium, 14,18 and mercury 17,19 from aqueous solutions. It was reported that the maximum adsorption capacity of chitosan for Hg 2þ was 815 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Chitosan is a hydrophilic, natural cationic polymer formed by the N-deacetylation of chitin, 7 which is present in fungi, insects, and crustaceans. Chitosan has been known for its metal adsorption properties since 1970s, 7,8 and it has been shown to effectively remove metals such as silver, 8 cadmium, 9 arsenic, 10 gold, 11,12 vanadium, 13 copper, [14][15][16] nickel, 14,17 chromium, 14,18 and mercury 17,19 from aqueous solutions. It was reported that the maximum adsorption capacity of chitosan for Hg 2þ was 815 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various new methods, the application of microemulsions is one of the most exciting and promising techniques 12 being used in separation, concentration and purification of proteins, extraction of metals, 13,14 adsorption of metals, 15,16 concentration of metals, 17 mineral flotation, 18 etc.…”
mentioning
confidence: 99%
“…One of these treatment techniques, sorption using convenient sorbents, is considered the extremely influential and economical method in relation to the simplicity of design and easiness of procedure. Tremendous concerted research efforts have been motivated to the development of new sorbents such as hydroxyapatite [24], activated carbon [23,25], chelating resin [26,27], clay [28,29], silica gel [30], zeolite [31], modified mineral sorbent [32], goethite [33], and certain polymer [34,35]. The extensively investigated sorbent is activated carbon with a great surface area, which is generated by heating carbon in the absence of air.…”
Section: Introductionmentioning
confidence: 99%